2020
DOI: 10.1186/s12888-020-02777-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parenting interventions on child and caregiver cortisol levels: systematic review and meta-analysis

Abstract: Background Nurturing care, in which children are raised in engaging and safe environments, may reduce child stress and shape hypothalamic-pituitary-adrenal axis functioning. Hence, parent-training programs may impact child cortisol levels, as well as behavioral, social and health outcomes. We conducted a systematic review of the impact of parent-training interventions on children’s and caregivers’ cortisol levels, and meta-analyzed the results. Methods In January 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 63 publications
1
23
1
8
Order By: Relevance
“…Together, these findings suggest a role for parenting sensitivity, as well as for individual differences within children, in the development of a coordinated physiological cortisol response (Blair et al, 2015). Finally, past research has documented null associations between young children's cortisol reactivity and overall positive parenting (i.e., warmth; Hackman et al, 2018) and a lack of discernible associations between parent-training interventions (none of which expressly focused on touch) and child cortisol levels (Martins et al, 2020). These findings, in combination with the strong associations between stress physiology and the more targeted behavior of positive physical touch in infancy (Feldman et al, 2014), lead us to evaluate whether positive touch in particular is associated with lower cortisol reactivity to stressors in early childhood.…”
Section: Cortisol As An Indicator Of Child Stress Reactivitymentioning
confidence: 85%
“…Together, these findings suggest a role for parenting sensitivity, as well as for individual differences within children, in the development of a coordinated physiological cortisol response (Blair et al, 2015). Finally, past research has documented null associations between young children's cortisol reactivity and overall positive parenting (i.e., warmth; Hackman et al, 2018) and a lack of discernible associations between parent-training interventions (none of which expressly focused on touch) and child cortisol levels (Martins et al, 2020). These findings, in combination with the strong associations between stress physiology and the more targeted behavior of positive physical touch in infancy (Feldman et al, 2014), lead us to evaluate whether positive touch in particular is associated with lower cortisol reactivity to stressors in early childhood.…”
Section: Cortisol As An Indicator Of Child Stress Reactivitymentioning
confidence: 85%
“…We replicated these results in a well-powered twin study, implementing a parenting intervention based on attachment theory and the social learning model of coercive cycles [ 1 , 37 ]. A recent meta-analysis of 19 parenting intervention studies found no significant effect on salivary cortisol [ 12 ]. The difference may be explained by the fact that salivary cortisol provides a snapshot of cortisol levels at a specific time or day, and cortisol levels are known to fluctuate substantially during and across days [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in 1- to 3-year-old children with high externalizing behavior, diurnal cortisol production as measured in saliva samples decreased after the VIPP-SD, specifically in carriers of the DRD4 7-allele [ 11 ]. However, in a recent meta-analysis of 19 parenting intervention studies, no overall significant effect of parenting interventions on child salivary cortisol levels was found [ 12 ]. Further work is needed to provide more robust evidence for the effectiveness of attachment-based parenting interventions on child externalizing behavior and stress regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The Stress and Developmental symposium discussed the feasibility of pivoting stress research in children to remote platforms and the role of parental care and childhood adversity on the regulation of stress-sensitive systems [ 27 , 28 , 29 , 30 ]. Presenters showed that stress reactivity in young children is not only moderated by the child’s mental health risk status but may also be buffered by parental presence during stress induction [ 29 ].…”
Section: Conference Sessionsmentioning
confidence: 99%
“…Presenters showed that stress reactivity in young children is not only moderated by the child’s mental health risk status but may also be buffered by parental presence during stress induction [ 29 ]. Although current findings are inconclusive [ 28 ], parental training interventions to enhance nurturing care have been proposed to help regulate stress-sensitive systems and to foster the wellbeing of the developing child. A sex and gender lens was also incorporated into this symposium, showing that early childhood maltreatment is robustly associated with revictimization among women; however, a more nuanced exploration of the type of maltreatment, the perpetrator (i.e., maternal or paternal), and sexual identity (monosexual vs. plurisexual) is integral to understanding how early childhood maltreatment may result in revictimization later in adulthood [ 30 ].…”
Section: Conference Sessionsmentioning
confidence: 99%